A NiO loaded Bi 3 O 4 Preparation method and application of Br nanosheet composite photocatalyst
By preparing bismuth-rich Bi3O4Br nanosheets and introducing nickel oxide, a composite photocatalyst supported by NiO-supported Bi3O4Br nanosheets was solved, and efficient CO2 reduction and methane selectivity were achieved.
Patent Information
- Application Number
- CN202310844070.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-07-11
AI Technical Summary
The application of BiOBr in CO2 photocatalytic reduction is limited by the problems of poor stability, low selectivity of product methane and low catalytic reduction activity.
By adjusting the acid-base, hydrothermal temperature and time of the mixed solution, bismuth-rich bismuth bromine oxide (Bi3O4Br) nanosheets were prepared, and nickel oxide was introduced through impregnation and calcination to form a composite photocatalyst supported by NiO-supported Bi3O4Br nanosheets.
The specific surface area and spectral utilization range of the catalytic system are improved, the CO2 reduction efficiency and methane selectivity are significantly improved, and the catalyst has good stability.
Smart Images

Figure CN117583003B_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a preparation method and application of a NiO-loaded Bi3O4Br nanosheet composite photocatalyst. Background Art
[0002] Global energy consumption has been growing over the past few decades, but the use of traditional fuels such as oil and coal has also brought about a variety of environmental problems, including excessive greenhouse gas emissions that have caused glacier melting, ecological imbalance and other environmental problems. Carbon dioxide (CO2) is one of the most common greenhouse gases. Converting it into chemicals with high added value is an effective way to utilize CO2, which is of great significance in offsetting the difficult-to-reduce CO2 and other greenhouse gas emissions. Since CO2 chemical molecules are very stable, their activation and reduction require overcoming large energy barriers, so there are high requirements for the catalytic method and the selection of catalysts.
[0003] Photocatalytic CO2 reduction (CO2PR) has the advantages of high catalytic efficiency and mild reaction conditions, and shows great application potential in the field of CO2 reduction. Bismuth oxyhalides (BiOX, X=Cl, Br, I) have a unique layered structure. The {X-Bi-O-Bi-X} nanolayers are stacked through non-bonded interactions. The space between the nanolayers is large, which can induce an internal electric field and is conducive to the separation and migration of photogenerated charges. Among the three types of bismuth oxyhalides (BiOCl, BiOBr and BiOI), BiOBr has a moderate band gap, which can achieve effective utilization of visible light and will not increase the recombination probability of photogenerated electron-hole pairs due to the narrow band gap. However, the application of BiOBr in CO2PR is still subject to some limitations, such as poor stability and low selectivity of the product methane (CH4). In addition, due to the positive conduction band minimum (CBM) of BiOX, its catalytic reduction activity is low, so a suitable modification strategy is needed.
[0004] In this regard, the present invention provides a method for preparing Bi3O4Br supported by nickel oxide. By adjusting the acidity and alkalinity of the mixed solution, the hydrothermal temperature and time, a bismuth-rich bismuth oxybromide (Bi3O4Br) is synthesized. On the one hand, the band gap is narrowed and the spectral utilization range is expanded; on the other hand, according to existing reports, the position of CBM is mainly determined by the Bi 6p orbital of BiOX, and the bismuth-rich strategy can effectively improve the CBM position of BiOX photocatalyst. In addition, nickel oxide is introduced by combining impregnation and calcination to form a Z-type heterojunction with Bi3O4Br, which is beneficial to the transfer of photogenerated charges and plays a positive role in the separation and transfer of carriers. The nanosheet morphology significantly increases the specific surface area of the catalyst, which can promote the utilization of visible light and the adsorption of CO2. Compared with the original bulk Bi3O4Br, the nickel oxide-supported Bi3O4Br nanosheets form a heterojunction structure, showing significantly improved CO2 reduction efficiency and product selectivity. The invention provides new insights into the conversion and utilization of CO2. Summary of the invention
[0005] The present invention provides a method for preparing nickel oxide-loaded Bi3O4Br nanosheets, using bismuth nitrate pentahydrate as a precursor, and preparing bismuth oxybromide nanosheets under hydrothermal conditions by a polyvinyl pyrrolidone self-assembly method; then using nickel nitrate hexahydrate as a nickel source, the nickel oxide-loaded Bi3O4Br nanosheets are prepared by a method combining impregnation and calcination. Under the optimal loading amount of nickel oxide, this catalytic system achieves a highly efficient photocatalytic effect of CO2 reduction. Under 4 hours of illumination, the methane (CH4) production reaches 8.45 μmol / g, and the CH4 selectivity is as high as 94.69%. The catalytic system still shows a continuous product production in a 16-hour extended reaction, and has good stability. The specific scheme is as follows:
[0006] A method for preparing NiO-loaded Bi3O4Br nanosheets, comprising:
[0007] 1) dispersing a certain amount of polyvinyl pyrrolidone and bismuth nitrate pentahydrate into a mannitol solution, dissolving a certain amount of sodium bromide in water, and slowly mixing the two solutions according to a molar ratio of Bi:Br of 3:1; adjusting the pH of the obtained milky white solution to 10.5-11.5; transferring the obtained solution to a hydrothermal kettle, placing the hydrothermal kettle in an oven to heat to 140-160°C, keeping the temperature for 12-24 hours, and after the hydrothermal kettle naturally cools to room temperature, washing the obtained sample with alcohol and water for several times, and drying it to obtain bismuth-rich bismuth oxybromide Bi3O4Br nanosheets;
[0008] 2) The Bi3O4Br nanosheets prepared by the above process are immersed in a certain amount of nickel nitrate hexahydrate aqueous solution, magnetically stirred for a period of time and then dried, and calcined in a muffle furnace at a predetermined temperature for a predetermined time to obtain NiO-loaded Bi3O4Br nanosheets.
[0009] Further, 0.4 g of polyvinyl pyrrolidone and 0.49 g of bismuth nitrate pentahydrate were weighed and dissolved in 30 mL of 0.1 mol / L mannitol solution, and 0.1029 g of sodium bromide was weighed and dissolved in 10 mL of water, and the two solutions were slowly mixed.
[0010] Further, 2 mol / L NaOH was used to adjust the pH of the milky solution to 11.5.
[0011] Furthermore, the hydrothermal autoclave was heated in an oven at 160°C for 24 h.
[0012] Furthermore, in the NiO-loaded Bi3O4Br nanosheets, the Bi3O4Br nanosheets are taken as 100% and the loading amount of NiO is 10-30wt%.
[0013] Furthermore, the temperature was increased to 400° C. at a heating rate of 5° C. / min in a muffle furnace and maintained for 3 h.
[0014] A method for photocatalytic reduction of carbon dioxide, characterized in that a predetermined mass of NiO-loaded Bi3O4Br nanosheets obtained by the preparation method is weighed, ultrasonically dispersed in deionized water, and dripped onto a glass fiber membrane; carbon dioxide is introduced into a photocatalytic reactor, an appropriate amount of deionized water is added, carbon dioxide is adsorbed on the catalyst surface under dark conditions, and then light is turned on for irradiation to achieve carbon dioxide conversion.
[0015] Furthermore, 20 mg of NiO-loaded Bi3O4Br nanosheets were weighed into a beaker, ultrasonically dispersed in 2 mL of deionized water, and added dropwise to the surface of a glass fiber filter membrane. The reactor was placed in a sealed glass reactor, and 95 kPa of carbon dioxide was introduced. The carbon dioxide was darkly adsorbed on the catalyst surface for 30 min. A 300 W xenon lamp was turned on for irradiation, and gas products were sampled and analyzed every hour.
[0016] The present invention has the following beneficial effects:
[0017] 1) Compared with bulk Bi3O4Br, the specific nanosheet structure obtained by the polyvinyl pyrrolidone self-assembly technology in the present invention greatly increases the specific surface area of the catalytic system, provides more active sites for the CO2 photocatalytic reduction reaction, thereby improving the utilization rate of visible light and the adsorption performance of CO2.
[0018] 2) Nickel oxide (NiO) was loaded onto Bi3O4Br nanosheets by a combination of impregnation and calcination, introducing additional active sites and greatly improving the yield and selectivity of the product CH4.
[0019] 3) The heterojunction structure formed between NiO and Bi3O4Br nanosheets greatly promotes the separation and migration of photogenerated charges, significantly reduces the band gap, and expands the spectral utilization range. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 XRD patterns of bulkBOB, BOB, NBOB-10, NBOB-15, and NBOB-20.
[0021] Figure 2 (a) SEM image of BOB; (b) TEM image of BOB; (c) SEM image of NBOB-15; (d) TEM image of NBOB-15; (ef) HRTEM image of NBOB-15; (g) Mapping diagram of Bi, O, Br, and Ni elements of NBOB-15.
[0022] Figure 3 (a) Methane production diagram of photocatalytic CO2 reduction by bulk BOB, BOB, NBOB-10, NBOB-15, and NBOB-20; (b) Total product amount diagram and methane selectivity diagram of photocatalytic CO2 reduction by bulk BOB, BOB, NBOB-10, NBOB-15, and NBOB-20.
[0023] Figure 4 XPS images of BOB and NBOB-15
[0024] Figure 5 (a) UV-Vis DRS graphs of bulkBOB, BOB, NBOB-10, NBOB-15, and NBOB-20; (b) Tauc graphs of NiO and BOB; (c) Tauc graphs of NBOB-10, NBOB-15, and NBOB-20; (d) VB-XPS graphs of BOB, NiO, and NBOB-15.
[0025] Figure 6 (a) EIS graphs of bulkBOB, BOB, NBOB-10, NBOB-15, and NBOB-20; (b) UV-visible diffuse reflectance spectra of BOB, NBOB-10, NBOB-15, and NBOB-20; (c) Fluorescence lifetime graphs of BOB, NBOB-10, NBOB-15, and NBOB-20.
[0026] Figure 7 Schematic diagram of the mechanism of photocatalytic CO2 reduction by NBOB.
[0027] Figure 8 NBOB-15 extended reaction time product yield diagram;
[0028] Fig. 9 XRD pattern of NBOB-15 after reaction.
[0029] Fig.10 XPS pattern of NBOB-15 after reaction. DETAILED DESCRIPTION
[0030] The present invention will be described in more detail below through specific embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0031] Example Preparation of NiO-supported Bi3O4Br nanosheets
[0032] Example 1
[0033] 0.4 g of polyvinyl pyrrolidone and 0.49 g of bismuth nitrate pentahydrate were weighed and dispersed in 30 mL of 0.1 mol / L mannitol solution, 0.1029 g of sodium bromide was dissolved in 10 mL of ultrapure water, and the two solutions were slowly mixed; the pH of the obtained milky white solution was adjusted to 11.5 with NaOH solution (2 mol / L); the obtained solution was transferred to a hydrothermal kettle, and the hydrothermal kettle was placed in an oven and heated at 160°C for 24 h. After it naturally cooled to room temperature, the obtained sample was washed with alcohol and water several times in sequence, and dried in an oven at 60°C to obtain Bi3O4Br nanosheets (BOB). 0.18 g of BOB was weighed and immersed in 0.0778 g of an aqueous solution of nickel nitrate hexahydrate. After magnetic stirring for 8 h, it was dried in an oven at 60 °C and maintained at 400 °C for 4 h in a muffle furnace at a heating rate of 5 °C / min to obtain bismuth oxybromide nanosheets loaded with 10 wt% nickel oxide, which were marked as NBOB-10.
[0034] Example 2
[0035] 0.4 g of polyvinyl pyrrolidone and 0.49 g of bismuth nitrate pentahydrate were weighed and dispersed in 30 mL of 0.1 mol / L mannitol solution, 0.1029 g of sodium bromide was dissolved in 10 mL of ultrapure water, and the two solutions were slowly mixed; the pH of the obtained milky white solution was adjusted to 11.5 with NaOH solution (2 mol / L); the obtained solution was transferred to a hydrothermal kettle, and the hydrothermal kettle was placed in an oven and heated at 160°C for 24 h. After it naturally cooled to room temperature, the obtained sample was washed with alcohol and water several times in sequence, and dried in an oven at 60°C to obtain Bi3O4Br nanosheets (BOB). 0.17 g of BOB was weighed and immersed in 0.0117 g of an aqueous solution of nickel nitrate hexahydrate. After magnetic stirring for 8 h, it was dried in an oven at 60 °C and maintained at 400 °C for 4 h in a muffle furnace at a heating rate of 5 °C / min to obtain 15 wt% nickel oxide-loaded bismuth oxybromide nanosheets, which were labeled as NBOB-15.
[0036] Example 3
[0037] 0.4 g of polyvinyl pyrrolidone and 0.49 g of bismuth nitrate pentahydrate were weighed and dispersed in 30 mL of 0.1 mol / L mannitol solution, 0.1029 g of sodium bromide was dissolved in 10 mL of ultrapure water, and the two solutions were slowly mixed; the pH of the obtained milky white solution was adjusted to 11.5 with NaOH solution (2 mol / L); the obtained solution was transferred to a hydrothermal kettle, and the hydrothermal kettle was placed in an oven and heated at 160°C for 24 h. After it naturally cooled to room temperature, the obtained sample was washed with alcohol and water several times in sequence, and dried in an oven at 60°C to obtain Bi3O4Br nanosheets (BOB). 0.16 g of BOB was weighed and immersed in 0.1560 g of an aqueous solution of nickel nitrate hexahydrate. After magnetic stirring for 8 h, it was dried in an oven at 60 °C and kept at 400 °C for 4 h in a muffle furnace at a heating rate of 5 °C / min to obtain 20 wt% nickel oxide-loaded bismuth oxybromide nanosheets, which were labeled as NBOB-20.
[0038] Comparative Example 1
[0039] Preparation of Bulk Bismuth Oxybromide
[0040] 0.9319 g Bi2O3 and 0.6098 g BiOBr were dissolved in 20 mL ethanol, mixed thoroughly and stirred for 30 min, centrifuged, dried and ground in a 60 °C oven, and then heated in a muffle furnace at a heating rate of 5 °C / min to 650 °C and maintained for 10 h to obtain bulk Bi3O4Br material, marked as bulkBOB.
[0041] Comparative Example 2
[0042] Preparation of Bi3O4Br nanosheets.
[0043] 0.4 g of polyvinyl pyrrolidone and 0.49 g of bismuth nitrate pentahydrate were weighed and dispersed in 30 mL of 0.1 mol / L mannitol solution, 0.1029 g of sodium bromide was dissolved in 10 mL of ultrapure water, and the two solutions were slowly mixed; the pH of the obtained milky white solution was adjusted to 11.5 with NaOH solution (2 mol / L); the obtained solution was transferred to a hydrothermal kettle, and the hydrothermal kettle was placed in an oven and heated at 160°C for 24 h. After it naturally cooled to room temperature, the obtained sample was washed with alcohol and water several times in sequence, and dried in an oven at 60°C to obtain Bi3O4Br nanosheets (BOB).
[0044] Comparative Example 3
[0045] Weigh 0.4g polyvinyl pyrrolidone and 0.49g bismuth nitrate pentahydrate and disperse them in 30mL of 0.1mol / L mannitol solution, dissolve 0.1029g sodium bromide in 10mL ultrapure water, and slowly mix the two solutions; the pH is 1.5; transfer the resulting solution to a hydrothermal kettle, place the hydrothermal kettle in an oven and heat it at 160°C for 12h, wait for it to naturally cool to room temperature, wash the resulting sample with alcohol and water several times in sequence, and dry it in an oven at 60°C to obtain BiOBr nanosheets.
[0046] Comparative Example 4
[0047] Weigh 0.4g polyvinyl pyrrolidone and 0.49g bismuth nitrate pentahydrate and disperse them in 30mL of 0.1mol / L mannitol solution, dissolve 0.1029g sodium bromide in 10mL ultrapure water, and slowly mix the two solutions; the initial pH is 9; transfer the resulting solution to a hydrothermal kettle, place the hydrothermal kettle in an oven and heat it at 140°C for 24h, wait for it to naturally cool to room temperature, wash the resulting sample with alcohol and water several times in turn, and dry it in an oven at 60°C to obtain Bi4O5Br2 nanosheets.
[0048] Comparative Example 5
[0049] Zinc oxide loaded Bi3O4Br
[0050] 0.4 g of polyvinyl pyrrolidone and 0.49 g of bismuth nitrate pentahydrate were weighed and dispersed in 30 mL of 0.1 mol / L mannitol solution, 0.1029 g of sodium bromide was dissolved in 10 mL of ultrapure water, and the two solutions were slowly mixed; the pH of the obtained milky white solution was adjusted to 11.5 with NaOH solution (2 mol / L); the obtained solution was transferred to a hydrothermal kettle, and the hydrothermal kettle was placed in an oven and heated at 160°C for 24 h. After it naturally cooled to room temperature, the obtained sample was washed with alcohol and water several times in sequence, and dried in an oven at 60°C to obtain Bi3O4Br nanosheets (BOB). 0.17 g of BOB was weighed and immersed in 0.1097 g of an aqueous solution of zinc nitrate hexahydrate, and then dried in an oven at 60°C after magnetic stirring for 8 h. The mixture was kept at 400°C for 4 h at a heating rate of 5°C / min in a muffle furnace to obtain 15 wt% zinc oxide-loaded bismuth oxybromide nanosheets (ZnO-BOB).
[0051] Comparative Example 6
[0052] Bi3O4Br (not prepared by the method of the present invention)
[0053] 1.5 mmol of bismuth nitrate pentahydrate was weighed and dissolved in 7.5 mL of acetic acid, and solution A was obtained after continuous stirring until it was completely dissolved; the above solution A was added into 60 mL of methanol, and 1.5 mmol of hexadecyltrimethylammonium bromide was added, and solution B was obtained after stirring; the above solution B was transferred to a 100 mL polytetrafluoroethylene-lined reactor and heated at 160°C for 24 hours; after the reaction was completed, the obtained precipitate was washed with deionized water and anhydrous ethanol for 3-4 times respectively, and then the product was dried in an oven at 60°C to obtain Bi3O4Br material, which was marked as BOB-no PVP.
[0054] Comparative Example 7
[0055] Nickel oxide is loaded on Bi3O4Br prepared by a method other than the method of the present invention
[0056] Weigh 1.5mmol of bismuth nitrate pentahydrate and dissolve it in 7.5mL of acetic acid, and stir continuously until it is completely dissolved to obtain solution A; add the above solution A to 60mL of methanol, and add 1.5mmol of hexadecyltrimethylammonium bromide, and stir to obtain solution B; transfer the above solution B to a 100mL polytetrafluoroethylene-lined reactor and heat it at 160°C for 24h; after the reaction is completed, wash the obtained precipitate with deionized water and anhydrous ethanol for 3-4 times respectively, and then dry the product in a 60°C oven to obtain BOB-no PVP.
[0057] 0.17 g of BOB-no PVP was weighed and immersed in 0.0117 g of an aqueous solution of nickel nitrate hexahydrate. After magnetic stirring for 8 h, it was dried in an oven at 60 °C and maintained at 400 °C for 4 h in a muffle furnace at a heating rate of 5 °C / min to obtain 15 wt% nickel oxide-loaded bismuth oxybromide nanosheets, which were marked as NBOB-no PVP.
[0058] Comparative Example 8
[0059] Nickel Oxide
[0060] 500 mg of nickel nitrate hexahydrate was dissolved in deionized water, 1 mol / L NaOH was added dropwise, and the pH was adjusted to 8 to generate Ni(OH)2 precipitate, which was aged at 55°C for 2 h, washed three times with deionized water, dried in an oven at 60°C for 12 h, and calcined in a muffle furnace at 400°C for 3 h to obtain NiO.
[0061] Experiments and Data
[0062] The activity investigation method of photocatalytic reduction of CO2 provided by the present invention is as follows:
[0063] 20 mg of Bi3O4Br supported by nickel oxide was weighed into a beaker, ultrasonically dispersed in 2 mL of deionized water, and dropped onto the surface of a glass fiber filter membrane. The mixture was placed in a sealed glass reactor, and 95 kPa of carbon dioxide was introduced. The carbon dioxide was darkly adsorbed on the catalyst surface for 30 minutes. A 300 W xenon lamp was turned on for irradiation, and gas products were sampled and analyzed every hour. In the 4-hour test, the performance of the embodiment and the comparative example is shown in the following table.
[0064] Table 1 Performance of the embodiments and comparative examples in a 4h photocatalytic CO2 reduction experiment
[0065]
[0066]
[0067] Figure 1 XRD patterns of bulk Bi3O4Br (bulkBOB), nanosheet Bi3O4Br (BOB) and Bi3O4Br nanosheets modified with different NiO loadings (NBOB-10, NBOB-15, NBOIB-20). The peaks at 23.9°, 29.04° and 31.44° correspond to the (112), (114) and (020) planes, respectively. After loading NiO, the diffraction peak intensity of the NBOB series materials decreases compared to BOB. On the one hand, this is due to the decrease in Bi3O4Br content; on the other hand, the NiO on the surface absorbs X-rays during the incident and reflection process. Due to the low loading and low crystallinity of NiO, the diffraction peaks of NiO are difficult to observe.
[0068] Figure 2 The SEM and TEM images of Example 2 and Comparative Example 1 are shown. It can be seen that the original BOB presents a regular square nanosheet morphology. After loading NiO, the surface and edge of the nanosheet are covered with NiO. From Figure (g), it can be seen that each element is evenly distributed.
[0069] Figure 3 The performance diagram of photocatalytic CO2 reduction of bulk BOB, BOB, NBOB-10, NBOB-15 and NBOB-20. First, compared with bulk BOB, the nanosheet structure significantly improves the photocatalytic CO2 reduction performance; second, after loading NiO, the target product CH4 yield and selectivity are significantly improved. NBOB-15 shows the highest CH4 selectivity and total product yield, with a CH4 selectivity of 94.69% and a CH4 yield of 8.12μmol·g -1 , CO production was 1.83 μmol·g -1 .
[0070] Figure 4 The XPS graphs of BOB and NBOB-15 are shown in Figure 1. In the Bi 4f graph, 158.25 eV (158.80 eV) and 163.56 eV (164.11 eV) are attributed to Bi 4f 7 / 2 with Bi 4f 5 / 2 In the O 1s graph, the peaks at 528.82eV (529.04eV) and 530.26eV (530.25eV) are attributed to the presence of lattice oxygen and adsorbed oxygen, respectively. In the Br 3d graph, the peaks at 67.70eV (68.14eV) and 68.79eV (69.05eV) can be attributed to the presence of Br 3d 5 / 2 With Br 3d 3 / 2 NBOB-15 has an additional peak at 66.62 eV, which may come from the interface interaction between NiO and BOB. In the Ni 2p diagram, 853.22 eV is Ni 2p 3 / 2 The main peak has two satellite bands, Sat I (855.02 eV) has an unclear origin and can be attributed to some surface defects, and Sat II (850.56 eV) is attributed to Ni 2+ ; 872.15eV is Ni 2p 1 / 2 The main peak of has a satellite band, Sat III (878.42 eV), which confirms that Ni exists in the form of oxide. After loading NiO, the binding energy of the XPS peaks of Bi and Br both shifted positively, and the electron cloud density decreased, indicating that electrons moved from BOB to NiO.
[0071] Figure 5(a) is the UV-Vis DRS diagram of bulkBOB, BOB, NBOB-10, NBOB-15, and NBOB-20. After loading NiO, the spectral utilization range of the NBOB series catalysts is significantly increased. Figure 5 (bc) are the Tauc plots of NiO, BOB, NBOB-10, NBOB-15 and NBOB-20, respectively. It can be seen that the band gap of BOB is 2.30 eV. After loading NiO, the band gaps of NBOB-10, NBOB-15 and NBOB-20 are significantly reduced; Figure 5 (d) is the VB-XPS graph of BOB, NiO, and NBOB-15, from which it can be seen that the valence band positions of the three are located at 1.12, 0.27, and 0.32 eV, respectively.
[0072] Figure 6 (a) is the EIS impedance diagram. As the NiO loading increases, NBOB-15 and NBOB-20 show a smaller arc radius, indicating that their impedance is small and the heterojunction structure is conducive to charge transfer. Figure 6 (b) is the UV-visible diffuse reflectance spectra of BOB, NBOB-10, NBOB-15, and NBOB-20. BOB exhibits the strongest PL intensity, while NBOB-15 has the weakest PL intensity, indicating that the heterojunction effectively promotes the separation of photogenerated charges. Figure 6 (c) shows the average fluorescence lifetime of NBOB-10, NBOB-15 and NBOB-20. The shortest fluorescence lifetime of NBOB-15 also indicates that the photogenerated charges are effectively separated in this catalytic system.
[0073] Figure 7 The schematic diagram of the mechanism of the catalytic system shows that a heterojunction structure is formed between BOB and NiO. Under light excitation, the electrons on the valence band of BOB recombine with the holes on NiO, which promotes the separation and migration of photogenerated charges. CO2 reacts with the photogenerated electrons and is converted into CO and CH4.
[0074] Figure 8 For the extended reaction time of NBOB-15, in the 16h reaction, CO showed a stable yield and the CH4 yield decreased slightly, but overall it still showed a continuous production.
[0075] Fig. 9 The XRD spectrum of NBOB-15 after the reaction. The peaks at 23.9°, 29.04° and 31.44° correspond to the (112), (114) and (020) planes of Bi3O4Br, respectively, indicating that the structure of this material has no obvious change after the reaction and is stable.
[0076] Fig.10The XPS spectrum of NBOB-15 after the reaction is shown in Figure 2. Compared with before the reaction, the XPS characteristic peaks of Bi, O, Br and Ni elements have no obvious changes, which indicates that this material has a high chemical stability.
[0077] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention.
Claims
1. A method for preparing a NiO-supported Bi3O4Br nanosheet composite photocatalyst for photocatalytic reduction of carbon dioxide, comprising: 1) dispersing a certain amount of polyvinyl pyrrolidone and bismuth nitrate pentahydrate into a mannitol solution, dissolving a certain amount of sodium bromide in water, and slowly mixing the two solutions according to a molar ratio of Bi:Br of 3:1; adjusting the pH of the obtained milky white solution to 10.5-11.5; transferring the obtained solution to a hydrothermal kettle, placing the hydrothermal kettle in an oven to heat to 140-160°C, keeping the temperature for 12-24 hours, and after the hydrothermal kettle naturally cools to room temperature, washing the obtained sample with alcohol and water for several times, and drying it to obtain bismuth-rich bismuth oxybromide Bi3O4Br nanosheets; 2) The Bi3O4Br nanosheets prepared by the above process are immersed in a certain amount of nickel nitrate hexahydrate aqueous solution, magnetically stirred for a period of time and then dried, and calcined in a muffle furnace at a predetermined temperature for a predetermined time to obtain NiO-loaded Bi3O4Br nanosheets.
2. The preparation method according to claim 1, wherein 0.4 g polyvinyl pyrrolidone and 0.49 g bismuth nitrate pentahydrate are dissolved in 30 mL 0.1 mol / L mannitol solution, 0.1029 g sodium bromide is dissolved in 10 mL water, and the two solutions are slowly mixed.
3. The preparation method according to claim 2, wherein the pH value of the milky solution is adjusted to 11.5 using 2 mol / L NaOH.
4. The preparation method according to claim 1, wherein the hydrothermal autoclave is heated in an oven at 160°C for 24 hours.
5. The preparation method as claimed in claim 1, wherein in the NiO-loaded Bi3O4Br nanosheets, the loading amount of NiO is 10-30wt%, based on 100% of the Bi3O4Br nanosheets.
6. The preparation method according to claim 1, wherein the temperature is increased to 400°C at a heating rate of 5°C / min in a muffle furnace and maintained for 3 hours.
7. A method for photocatalytic reduction of carbon dioxide, characterized in that: A predetermined mass of NiO-loaded Bi3O4Br nanosheet composite photocatalyst obtained by the preparation method according to any one of claims 1 to 6 is weighed, ultrasonically dispersed in deionized water, and dropped onto a glass fiber membrane. Carbon dioxide is introduced into a photocatalytic reactor, and an appropriate amount of deionized water is added. Carbon dioxide is adsorbed on the catalyst surface under dark conditions, and then a light is turned on to achieve carbon dioxide conversion.
8. The method as claimed in claim 7, weighing 20 mg of NiO-loaded Bi3O4Br nanosheet composite photocatalyst into a beaker, ultrasonically dispersing it in 2 mL of deionized water, dropping it on the surface of a glass fiber filter membrane, placing it in a sealed glass reactor, passing 95 kPa of carbon dioxide, allowing carbon dioxide to adsorb on the catalyst surface in the dark for 30 minutes, turning on a 300 W xenon lamp for irradiation, and sampling and analyzing gas products every hour.
Citation Information
Patent Citations
CO2 low-temperature methanation catalyst, preparation and application thereof
CN109529840A